Effects of stigma on the mental health of adolescents orphaned by AIDS. - Cluver, L; Gardner, F; Operario, D (2008)
PURPOSE: By 2010, an estimated 18.4 million children in Sub-Saharan Africa will be orphaned by AIDS. Research in South Africa shows that AIDS orphanhood is independently associated with heightened levels of psychological problems. This study is the first to explore the mediating effects of stigma and other factors operating on a community level, on associations between AIDS orphanhood and mental health. We assessed the associations of four risk factors that can potentially be addressed at a community level (bullying, stigma, community violence, and lack of positive activities) with psychological problems and orphanhood status. METHOD: One thousand twenty-five participants aged 10-19 were recruited from deprived urban settlements in South Africa. The sample included adolescents orphaned by AIDS (n = 425), adolescents orphaned by non-AIDS causes (n = 241), and nonorphaned adolescents (n = 278). Participants were interviewed using standardized psychological measures of depression, anxiety, posttraumatic stress, peer problems, delinquency, and conduct problems. Information on risk factors and demographic characteristics were also assessed. RESULTS: AIDS-orphaned adolescents reported higher levels of stigma and fewer positive activities than other groups. There were no reported differences on bullying or community violence. All community-level risk factors were associated with poorer psychological outcomes. Multivariate analyses controlling for age and gender showed that experience of stigma significantly mediated associations between AIDS orphanhood and poor psychological outcomes. CONCLUSIONS: Reduction of AIDS-related stigma could potentially reduce adverse psychological outcomes among AIDS-orphaned adolescents.